Instructional Time Loss in Developing Countries - Abadzi, Helen (World Bank, 2012)
Students in developing countries are often taught for only a fraction of the intended number of school hours. Time is often wasted due to informal school closures, teacher absenteeism, delays, early departures, and poor use of classroom time. Since the 1970s, attempts have been made in several countries to measure the use of instructional time in schools and its impact on student achievement. Studies have been of variable quality and have used different definitions and methods. However, they have consistently shown that significant amounts of time are lost and that the amount of time spent engaged in learning tasks is related to student performance. The large losses in many countries raise issues of governance, monitoring, and validity of economic analyses. It is important to take instructional time wastage into account when considering public sector expenditures on education, teacher salary rates, unit costs, and the rates of return from graduates. Refining time-loss measurement methods and disseminating policy implications may improve the efficiency of educational systems worldwide.